الفعل(أصْبَحَ) في القرآن الكريم دراسة نحويَّة دلاليَّة - Mustafa, Babiker (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2025)
Research title: (The verb (asbaha) in the Holy Qur’an, a grammatical and semantic study) Its importance: The importance of the topic appears in the reactions (asbaha) imperfect and complete, with different meanings. Its objectives: Study the verb (asbaha) in the Holy Qur’an ,His method: descriptive. The most important results: The verb (asbaha) was incomplete in the sense of “became” in thirteen places, it was incomplete in the meaning of entering the morning time in seven places, the present tense (usbiho-tosbiho) in five places, and the active participle (musbih) was in five places. It is possible that (asbaha) decreases and completes according to the grammatical guidance And the semantic meaning. Among the recommendations: are for students of the Arabic language to research the Holy Qur’an to learn the secrets of the language, and for researchers to study nouns, verbs and letters to understand the grammatical and semantic aspects, and for those interested to study the remaining missing verbs in the Holy Qur’an.